Perbandingan Konsep Talak Menurut Fikih Klasik dan Kompilasi Hukum Islam - Fajar Durun Nafis; Iip Nur Fahmi; Zulfa Adzillan Nuha; Samsul Bahri; Novi Laela Sugiman (Penerbit Lestari Sakha Pustaka, 2026)
Talaq is one of the instruments for the dissolution of marriage regulated both in classical fiqh and the Compilation of Islamic Law (KHI). The conceptual differences between the two often create problems among Indonesian society. This study aims to analyze and compare the concept of talaq according to classical fiqh and KHI comprehensively, covering aspects of definition, conditions and pillars, classification, procedures, and legal consequences of talaq. This is a normative legal research employing statutory, conceptual, and comparative approaches. Data sources consist of primary legal materials including KHI, Law No. 1 of 1974, and classical fiqh books, as well as secondary legal materials comprising journals and related literature. Data analysis was conducted using qualitative descriptive-analytical methods. The findings reveal that classical fiqh and KHI share similarities in the classification of talaq types but differ fundamentally in three aspects: first, classical fiqh positions talaq as the husband's prerogative right exercisable without court involvement, whereas KHI requires the talaq pledge before the Religious Court; second, triple talaq pronounced simultaneously is considered valid as three by the majority of classical fiqh scholars, while KHI counts it as one; third, the wife's post-divorce rights under KHI are only guaranteed through court mechanisms. The transformation from classical fiqh to KHI represents a legal development oriented toward public interest and the protection of women's rights.